Rating shopping: evidence from the Chinese corporate debt security market. (6th July 2020) - Chang, Zhang; Hu, Xiaolu; Pan, Zheyao; Shi, Jing
Abstract: We provide the first direct evidence on how issuers choose a credit rating agency (CRA). Using rating data from a leading CRA in China, we find that although in most cases the issuers publish more favourable ratings, in some cases issuers just select the ratings provided by CRAs they have business relationships with, especially when the more favourable ratings are above issuers' prior ratings. Our further analysis suggests that this phenomenon is driven by the switching cost arising from the issuer being considered as a rating shopper when it obtains an upgrade from a CRA without a business relationship.